Chaperones GroEL/GroES Accelerate the Refolding of a Multidomain Protein through Modulating On-pathway Intermediates - Dahiya, Vinay (American Society for Biochemistry and Molecular Biology, 2014)
Despite a vast amount information on the interplay of GroEL, GroES, and ATP in chaperone-assisted folding, the molecular details on the conformational dynamics of folding polypeptide during its GroEL/GroES-assisted folding cycle is quite limited. Practically no such studies have been reported to date on large proteins, which often have difficulty folding in vitro. The effect of the GroEL/GroES chaperonin system on the folding pathway of an 82-kDa slow folding protein, malate synthase G (MSG), was investigated. GroEL bound to the burst phase intermediate of MSG and accelerated the slowest kinetic phase associated with the formation of native topology in the spontaneous folding pathway. GroEL slowly induced conformational changes on the bound burst phase intermediate, which was then transformed into a more folding-compatible form. Subsequent addition of ATP or GroES/ATP to the GroEL-MSG complex led to the formation of the native state via a compact intermediate with the rate several times faster than that of spontaneous refolding. The presence of GroES doubled the ATP-dependent reactivation rate of bound MSG by preventing multiple cycles of its GroEL binding and release. Because GroES bound to the trans side of GroEL-MSG complex, it may be anticipated that confinement of the substrate underneath the co-chaperone is not required for accelerating the rate in the assisted folding pathway. The potential role of GroEL/GroES in assisted folding is most likely to modulate the conformation of MSG intermediates that can fold faster and thereby eliminate the possibility of partial aggregation caused by the slow folding intermediates during its spontaneous refolding pathway.